TEACHING COURSES ONLINE: HOW MUCH TIME DOES IT TAKE? - Lazarus, Belinda Davis (Online Learning, 2003)
Studies show that temporal factors like workload and lack of release time inhibit faculty participation in developing and teaching online courses; however, few studies exist to gauge the time commitment. This longitudinal case study, presented at the Seventh Annual Sloan-C International Conference on ALN, examined the amount of time needed to teach three asynchronous online courses at The University of Michigan-Dearborn from Winter 1999 through Winter 2000. Twenty-five students were enrolled in each course. Self-monitoring was used to measure the amount of time required to complete the following activities: 1) reading and responding to emails; 2) reading, participating in, and grading 10 online discussions; and 3) grading 15 assignments. Using a stopwatch, the investigator timed and recorded the number of minutes needed for each activity. Also, all messages and assignments were archived and frequency counts were recorded. The weekly, mean number of minutes and assignments was entered on line graphs for analysis. The data showed that teaching each online course required 3 to 7 hours per week, with the greatest number of emails and amount of time required during the first and last 2-weeks of the semesters. Participation in and grading of the discussions took the greatest amount of time and remained steady across the semester. However unlike many live courses, the students participated more in the discussions than the instructor did. The number of assignments that were submitted each week steadily increased over each semester. This case study indicates that the time needed to teach online courses falls within the range of reasonable expectations for teaching either live or online courses and represents the beginning of this area of inquiry. Consequently, additional studies are needed with a variety of instructors across a variety of courses and disciplines to further pinpoint faculty time commitment.